Double Asymmetric Core Optimizes Crystal Packing to Enable Selenophene‐based Acceptor with Over 18 % Efficiency in Binary Organic Solar Cells. (25th January 2023) - Zhao, Xin; An, Qiaoshi; Zhang, Heng; Yang, Can; Mahmood, Asif; Jiang, Mengyun; Jee, Min Hun; Fu, Bin; Tian, Shiyu; Woo, Han Young; Wang, Yapei; Wang, Jin‐Liang
Abstract: Side‐chain tailoring is a promising method to optimize the performance of organic solar cells (OSCs). However, asymmetric alkyl chain‐based small molecular acceptors (SMAs) are still difficult to afford. Herein, we adopted a novel asymmetric n ‐nonyl/undecyl substitution strategy and synthesized two A‐D1 A′D2 ‐A double asymmetric isomeric SMAs with asymmetric selenophene‐based central core for OSCs. Crystallographic analysis indicates that AYT9Se11‐Cl forms a more compact and order intermolecular packing compared to AYT11Se9‐Cl, which contributed to higher electron mobility in neat AYT9Se11‐Cl film. Moreover, the PM6 : AYT9Se11‐Cl blend film shows a better morphology with appropriate phase separation and distinct face‐on orientation than PM6 : AYT11Se9‐Cl . The OSCs with PM6 : AYT9Se11‐Cl obtain a superior PCE of 18.12 % compared to PM6 : AYT11Se9‐Cl (17.52 %), which is the best efficiency for the selenium‐incorporated SMAs in binary BHJ OSCs. Our findings elucidate that the promising double asymmetric strategy with isomeric alkyl chains precisely modulates the crystal packing and enhances the photovoltaic efficiency of selenophene‐incorporated SMAs. Abstract : Two isomeric A‐D1 A′D2 ‐A type double asymmetric selenophene‐based small molecule acceptors (SMAs) were synthesized by a n ‐nonyl/undecyl regioisomeric strategy to optimize single‐crystal packing, improve film morphology, and boost device performance. PM6 : AYT9Se11‐Cl achieved a superior PCE of 18.12 % compared to PM6 : AYT11Se9‐Cl .